Lengua Azul - Jorge R. Rey; Walter J. Tabachnick; Chelsea T. Smartt; C. Roxanne Rutledge-Connelly (EDIS, 2008)
ENY-743S, a 5-page illustrated fact sheet by Jorge R. Rey, Walter J. Tabachnick, Chelsea T. Smartt, and C. Roxanne Connelly, is the Spanish language version of ENY-743/IN768 Bluetongue. It answers common questions about this viral disease of ruminant livestock transmitted by biting midges, the virus, clinical signs of bluetongue, economic impact, transmission, diagnosis, cure, distribution, presence in Florida, and prevention. Includes references. Published by the UF Department of Entomology and Nematology, June 2008.